Make the substitution z = 3^x. The equation becomes
z^2 + 3*z - 4 = 0
This can be factored:
(z + 4)*(z - 1) = 0
z = -4, z = 1
3^x = -4, 3^x = 1 for the second of these, x = 0. The other root is imaginary: take log of both sides
x*log(3) = log(-4), x = log(-4)/log(3) = [log(4) + log(-1)]/log(3)= log(4)/log(3) + log(-1)/log(3)
Using natural logs, log(4) = 1.386, log(3) = 1.099, and since e^πi = -1, log(-1) = πi, so the other root is
1.262 + (π/3)i
2007-04-27 13:14:50
·
answer #1
·
answered by gp4rts 7
·
0⤊
0⤋